Vitamin D in Health and Disease - Giuseppe Murdaca; Sebastiano Gangemi (Biomedicines, 2022)
Vitamin D (VD) is a fat-soluble hormone that plays a fundamental role not only in calcium homeostasis and bone metabolism, but also has anti-inflammatory and antioxidant properties, acting on both innate and adaptive immunity [...]